2021
DOI: 10.2147/jir.s330157
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Modified-Curcumin Promotes Resolvin-Like Activity and Reduces Bone Loss in Diabetes-Induced Experimental Periodontitis

Abstract: Purpose: Clinically, it is challenging to manage diabetic patients with periodontitis. Biochemically, both involve a wide range of inflammatory/collagenolytic conditions which exacerbate each other in a "bi-directional manner." However, standard treatments for this type of periodontitis rely on reducing the bacterial burden and less on controlling hyperinflammation/excessive-collagenolysis. Thus, there is a crucial need for new therapeutic strategies to modulate this excessive host response and to promote enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…The advantages of this compound over the natural CUR includes greater efficacy as an MMP inhibitor and improved bioavailability. There was a consensus among the three studies, confirming the impact of CMC2.24 on bone loss reduction and inflammatory markers, where the activity of MMPs and the levels of pro-inflammatory cytokines were inhibited [22][23][24]. The outcomes of the mentioned studies confirmed that administration of CMC2.24 has an anti-inflammatory effect, and suggests it as an efficacious treatment for reducing bone resorption.…”
Section: Resveratrolmentioning
confidence: 59%
See 2 more Smart Citations
“…The advantages of this compound over the natural CUR includes greater efficacy as an MMP inhibitor and improved bioavailability. There was a consensus among the three studies, confirming the impact of CMC2.24 on bone loss reduction and inflammatory markers, where the activity of MMPs and the levels of pro-inflammatory cytokines were inhibited [22][23][24]. The outcomes of the mentioned studies confirmed that administration of CMC2.24 has an anti-inflammatory effect, and suggests it as an efficacious treatment for reducing bone resorption.…”
Section: Resveratrolmentioning
confidence: 59%
“…no change; ANI, animal study; CLIN, clinical study; ABL, alveolar bone loss; BG, blood glucose; CAL, clinical attachment level; CMC2.24, chemically modified curcumin; DM, diabetes mellitus; HbA1c, hemoglobin A1c; IL, interleukin; INS, insulin; MAPK, mitogen-activated protein kinase; MMPs, matrix metalloproteinases; PD, pocket depth; RANKL/OPG, receptor activator of nuclear factor-kappa B ligand/osteoprotegerin; SIRT, silent information regulator; sost, sclerostin; SRP, non-surgical scaling and root planning. This review identified three animal studies that evaluated the effect of a chemically modified curcumin (CMC2.24) on DP [22][23][24]. CMC2.24 is a phenylamino carbonyl curcumin, which is tri-ketonic in contrast to di-ketonic natural curcumin compounds.…”
Section: Resveratrolmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding genetic expression of inflammatory immune factors, Southerland et al (Southerland et al, 2000) state that increased Advanced Glycation End Produtcts (AGE), because of the hyperglycemic state associated with an inflammatory host response, is the cause of the exacerbation of diabetes systemic complications and severity of periodontal disease (Deng et al, 2021). The AGE-RAGE (RAGE -receptors for AGE) interactions result in the production of inflammatory mediators such as IL-1β, TNF-α and IL-6, and enzymes like MMPs which are responsible for bone resorption (Preshaw & Taylor, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Many phytochemicals have been reported to exert protective effects on bone cells and osteoporosis animal models through activation of HO-1 ( Haines et al, 2012 ; Su et al, 2013 ). Among them, the most promising drug candidates are curcumin and resveratrol, both of which have been suggested to be effective in the treatment of osteoporosis in laboratory, translational and clinical studies (see Table 3 ) ( Deng et al, 2021 ; Moschen and Shakibaei, 2013 ; Sharan et al, 2009 ). In a double-blind randomized controlled trial (RCT), postmenopausal osteoporotic women treated with the combination of curcumin and alendronate showed significant increases in total hip, lumbar spine and femoral neck BMDs accompanied by increased bone turnover markers ( Khanizadeh et al, 2018 ).…”
Section: Therapeutic Modulation Of Ho-1 In Osteoporosismentioning
confidence: 99%